The effects of non-performing loans on bank stability and economic performance in Zimbabwe - Katuka, Blessing; Mudzingiri, Calvin; Vengesai, Edson (Asian Economic and Financial Review, 2023)
This study explores the impact of non-performing loans (NPLs) on the Zimbabwean banking industry’s stability and economic performance during the dollarization era. The panel vector autoregressive (PVAR) model was applied using annual data from 2009 to 2017. The findings indicated that short-run NPL shocks negatively impact the risk-adjusted return, while the impact on risk-adjusted capitalization is positive but dies off in the long run. The findings from the paper further show that NPLs have a strong negative and significant effect on loan growth and economic performance in the short run but remain muted in the long run. The study results also show a bi-directional causality between banking industry stability and NPLs. In summary, NPLs affect banking industry stability, loan growth and economic performance in Zimbabwe. A possible implication is the formulation of a sound regulatory framework that curbs the increase in NPLs, promotes stability within the banking industry, and improves economic performance. The practical implication is that banks must get it right the first time regarding bank lending policies. Thus, the study recommends that Zimbabwean banks proactively manage their exposure to non-performing loans by implementing rigorous credit risk assessment processes.